Challenging Carbon Lock-In: Insights From U.S. Governmental Energy Research and Development Expenditures With Advocacy Recommendations for the Energy Research Community - Robertson, Ashley M. (Frontiers in Climate, 2022)
The United States relies heavily on fossil and nuclear energy to meet its burgeoning electricity generation demands. The incumbent institutional and industrial power dynamics may support a fossil and nuclear energy status quo and has shown signs of carbon lock-in. Government research and development (R&D) funding can either be a help or hinderance to institutional carbon lock-in. This analysis investigates the link between the Department of Energy’s historical funding allocations for energy research programs in the fossil, nuclear, and renewable energy sector and the federal government's tendency to support entrenched, carbon-based energy systems. While the Department of Energy's renewable energy programs have received more funding in recent years, this investment alone is not enough currently to thwart carbon lock-in. Thus, this paper recommends suggestions for researchers to advocate for more renewable energy research and development resources through personal, professional, and institutional strategies to spur decarbonization.